Florida Wax Scale, Ceroplastes floridensis Comstock: EENY-510/IN913, 12/2011 - Sharma, Shweta; Buss, Eileen (EDIS, 2012)
The Florida wax scale, Ceroplastes floridensis Comstock, is one of the most commonly encountered soft scales throughout the southern United States, where it is a serious pest of citrus and several ornamental and landscape plants, like holly. This 4-page fact sheet was written by Shweta Sharma and Eileen Buss, and published by the UF Department of Entomology and Nematology, December 2011. EENY-510/IN913: Florida Wax Scale, Ceroplastes floridensis Comstock (ufl.edu)